The role of Islamic faith-based institutions in collaborative governance to prevent stunting in Indonesia - Kurnia, Galuh Mega; Muthmainnah, Muthmainnah; Qomaruddin, Mochammad Bagus; Wulandari, Fatqiatul; Zari, Afina Puspita (Indonesian Journal of Islam and Muslim Societies, 2026)
The dynamics of collaborative governance in accelerating stunting reduction in Madiun City involve various key actors, primarily the Stunting Reduction Acceleration Team (TPPS), the National Zakat Agency (BAZNAS), and the Office of Religious Affairs (KUA). This situation indicates that Islamic faith-based institution have a strong contribution to supporting the government in improving public health and creating a quality generation of Muslim society. This study aims to explore the role of BAZNAS and KUA in collaborative governance efforts to accelerate stunting reduction in Madiun City. This research was conducted using a case study approach through in-depth interviews with 49 TPPS actors at the city, sub-district, and village levels, as well as representatives from BAZNAS and KUA. The results show that KUA contributes through communicating religion-based behavior change to prospective brides, teenagers, and religious communities. Meanwhile, BAZNAS implements a zakat-based program that provides economic and environmental support for vulnerable families. The implementation of collaborative governance involving the government and Islamic institutions is in accordance with the Medina Charter drafted by the Prophet Muhammad, which emphasizes cross-sectoral collaboration to achieve community welfare. The involvement of BAZNAS is also in line with the values of Islamic teachings, which hold that zakat is a social instrument for community welfare. Education conducted by the KUA strengthens the community’s foundation in building a harmonious, loving, and compassionate household. Collaboration involving religious institutions offers a culturally grounded and sustainable approach to achieving targets in SDG 3 (Good Health and Well-being), SDG 1 (No Poverty), and SDG 17 (Partnerships for the Goals), particularly in Muslim-majority contexts. Dinamika collaborative governance dalam upaya percepatan penurunan stunting di Kota Madiun melibatkan peran berbagai aktor kunci, utamanya Tim Percepatan Penurunan Stunting (TPPS), Badan Amil Zakat Nasional (BAZNAS), dan Kantor Urusan Agama (KUA). Kondisi tersebut menunjukkan bahwa instansi agama islam memiliki kontribusi yang kuat untuk dalam mendukung pemerintah meningkatkan kesehatan masyarakat dan mewujudkan generasi Islami yang berkualitas. Penelitian ini bertujuan untuk mengeksplorasi peran BAZNAS dan KUA dalam collaborative governance untuk upaya percepatan penurunan stunting di Kota Madiun. Penelitian ini dilakukan dengan pendekatan studi Kasus melalui wawancara mendalam dengan 49 aktor TPPS di tingkat kota, kecamatan, dan kelurahan, serta perwakilan dari BAZNAS dan KUA. Hasil penelitian menunjukkan bahwa KUA berkontribusi pada pencegahan stunting melalui komunikasi perubahan perilaku berbasis agama kepada calon pengantin, remaja, dan komunitas keagamaan. Sementara itu, BAZNAS melaksanakan program berbasis zakat yang memberikan dukungan ekonomi dan lingkungan bagi keluarga rentan. Implementasi collaborative governance yang melibatkan pemerintah dan lembaga keagamaan sesuai dengan Piagam Madinah yang disusun oleh Nabi Muhammad SAW, yang menekankan kerjasama lintas sektor untuk mewujudkan kesejahteraan masyarakat. Pelibatan BAZNAS juga sejalan dengan nilai yang terkandung dalam ajaran Islam bahwa zakat adalah instrumen sosial untuk kesejahteraan masyarakat. Edukasi yang dilakukan oleh KUA menguatkan fondasi masyarakat dalam membangun rumah tangga yang sakinah, mawaddah, warrahmah. Kolaborasi melibatkan lembaga keagamaan yang menawarkan pendekatan yang berlandaskan budaya dan berkelanjutan untuk mencapai target dalam SDG 3 (Kesehatan dan Kesejahteraan yang Baik), SDG 1 (Pengentasan Kemiskinan), dan SDG 17 (Kemitraan untuk Mencapai Tujuan), khususnya dalam konteks mayoritas Muslim.